Validasi Klinik Strenghts and Difficulties Questionnaire (SDQ) sebagai Instrumen Skrining Gangguan Tingkah Laku - Oktaviana, Mistety; Wimbarti, Supra (Jurnal Psikologi, 2014)
Conduct Disorder is one of the most common problems often found in children taken to Puskesmas. Based on SIKM (Mental Health Information System) from 2011 to May 2013, 46.3% of those taken to Puskesmas in Sleman and Yogyakarta were identified with behavioral and emotional disorder. Therefore, screening instrument is needed for early identifying conduct disorder in them. Strengths and Difficulties Questionnaire (SDQ) has been developed to meet the need. The SDQ is a 25-item questionnare about the positive and negative atributes of children and adolescents (4-16 years old). This study aimed to adapt the English version of SDQ-Teacher Reports (TR) into Indonesian version and to examine psychometrical properties and clinical validation of the Indonesian version for screening conduct disorder. The subjects were 161 Elementary students from Sleman and Yogyakarta, boys and girls of 7-13 years old of age. The reliability coeficient using Alpha Cronbach was Î±=0,773, and the construct validity using Principal Axis Factoring (PAF) showed that SDQ-TR had six structural factors. Clinical validation using Receiver Operating Curve (ROC) revealed that the value of sensitivity were 0.67 with spesificity 0.68 (for the optimum cut-off point â‰¥5), and using Likelihood Ratio (LR) showed LR (+) was 2.09 and LR (-) was 0.49. Keywords: children, clinical validation, conduct disorder, SDQ-TR